2022
DOI: 10.3390/ijerph192215336
|View full text |Cite
|
Sign up to set email alerts
|

Older Black Lesbians’ Needs and Expectations in Relation to Long-Term Care Facility Use

Abstract: There is a dearth of long-term care research that focuses on the expectations and experiences of older sexual minority (SM) adults. That research dwindles further when examining subgroups within that population such as older Black lesbians. The purpose of this study was to explore older Black lesbians’ needs and expectations in relation to the utilization of long-term care (LTC) facilities. We conducted secondary data analysis using data from 14 focus groups that discussed health and aging with older Black les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
4
7
0
Order By: Relevance
“…Most reported long-term care plans that included housing and institutions, private medical or long-term care insurance, financial planning and medical decisions. Previous studies conducted with older lesbians in the United States reported similar findings (Hash & Netting, 2007;Lowers, 2017;Singleton et al, 2022). In Taiwan, there is no LGBT or…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…Most reported long-term care plans that included housing and institutions, private medical or long-term care insurance, financial planning and medical decisions. Previous studies conducted with older lesbians in the United States reported similar findings (Hash & Netting, 2007;Lowers, 2017;Singleton et al, 2022). In Taiwan, there is no LGBT or…”
Section: Discussionsupporting
confidence: 68%
“…Some older black lesbians expressed plans of moving to a long-term care facility (e.g. a nursing home or an assisted living facility) when they were no longer able to care for themselves (Singleton et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations